David und Salomon im Koran: ein Komparativ-theologischer Ansatz - Saad, Nadia (Erlanger Jahrbuch für Interreligiöse Diskurse. Methoden der Darstellung und Analyse interreligiöser Diskurse)

I-AID: Identifying Actionable Information From Disaster-Related Tweets - Zahera, H.M.A; Jalota, Rricha; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science

ASSET: A Semi-supervised Approach for Entity Typing in Knowledge Graphs - Zahera, H.M.A; Heindorf, Stefan; Ngomo, Axel-Cyrille Ngonga (Proceedings of the 11th on Knowledge Capture Conference)

Essays on Modeling Languages and Software Tools for Business Model Innovation: Theory and Empirical Evidence - Szopinski, Daniel

Decomposition-Guided Reductions for Argumentation and Treewidth - Fichte, Johannes; Hecher, Markus; Mahmood, Yasir; Meier, Arne (Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence)
Argumentation is a widely applied framework for modeling and evaluating arguments and its reasoning with various applications. Popular frameworks are abstract argumentation (Dung’s framework) or logic-based argumentation (Besnard-Hunter’s framework). Their computational complexity has been studied quite in-depth. Incorporating treewidth into the complexity analysis is particularly interesting, as solvers oftentimes employ SAT-based solvers, which can solve instances of low treewidth fast. In this paper, we address whether one can design reductions from argumentation problems to SAT-problems while linearly preserving the treewidth, which results in decomposition-guided (DG) reductions. It turns out that the linear treewidth overhead caused by our DG reductions, cannot be significantly improved under reasonable assumptions. Finally, we consider logic-based argumentation and establish new upper bounds using DG reductions and lower bounds.

Parameterised complexity of model checking and satisfiability in propositional dependence logic - Mahmood, Yasir; Meier, Arne (Annals of Mathematics and Artificial Intelligence)
Abstract Dependence Logic was introduced by Jouko Väänänen in 2007. We study a propositional variant of this logic (PDL) and investigate a variety of parameterisations with respect to central decision problems. The model checking problem (MC) of PDL is NP -complete (Ebbing and Lohmann, SOFSEM 2012). The subject of this research is to identify a list of parameterisations (formula-size, formula-depth, treewidth, team-size, number of variables) under which MC becomes fixed-parameter tractable. Furthermore, we show that the number of disjunctions or the arity of dependence atoms (dep-arity) as a parameter both yield a paraNP-completeness result. Then, we consider the satisfiability problem (SAT) which classically is known to be NP -complete as well (Lohmann and Vollmer, Studia Logica 2013). There we are presenting a different picture: under team-size, or dep-arity SAT is paraNP -complete whereas under all other mentioned parameters the problem is FPT . Finally, we introduce a variant of the satisfiability problem, asking for a team of a given size, and show for this problem an almost complete picture.
Keywords: Applied Mathematics; Artificial Intelligence

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Accounting for Heuristics in Reputation Systems: An Interdisciplinary Approach on Aggregation Processes - van Straaten, Dirk; Melnikov, Vitalik; Hüllermeier, Eyke; Mir Djawadi, Behnud; Fahr, René
Aggregation metrics in reputation systems are important for overcoming information overload. When using these metrics, technical aggregation functions such as the arithmetic mean are implemented to measure the valence of product ratings. However, it is unclear whether the implemented aggregation functions match the inherent aggregation patterns of customers. In our experiment, we elicit customers' aggregation heuristics and contrast these with reference functions. Our findings indicate that, overall, the arithmetic mean performs best in comparison with other aggregation functions. However, our analysis on an individual level reveals heterogeneous aggregation patterns. Major clusters exhibit a binary bias (i.e., an over-weighting of moderate ratings and under-weighting of extreme ratings) in combination with the arithmetic mean. Minor clusters focus on 1-star ratings or negative (i.e., 1-star and 2-star) ratings. Thereby, inherent aggregation patterns are neither affected by variation of provided information nor by individual characteristics such as experience, risk attitudes, or demographics.

Incentive Schemes in Customer Rating Systems - Comparing the Effects of Unconditional and Conditional Rebates on Intrinsic Motivation - van Straaten, Dirk

Fighting Fire with Fire - Overcoming Ambiguity Aversion by Introducing more Ambiguity - van Straaten, Dirk; Fahr, René

Political Speaker Transfer: Learning to Generate Text in the Styles of Barack Obama and Donald Trump - Bülling, Jonas

Computational Text Professionalization using Neural Sequence-to-Sequence Models - Mishra, Avishek

ReconOS64: High-Performance Embedded Computing for Industrial Analytics on a Reconfigurable System-on-Chip - Clausing, Lennart (Proceedings of the 11th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Relaxed parameter conditions for chemotactic collapse in logistic-type parabolic–elliptic Keller–Segel systems - Black, Tobias; Fuest, Mario; Lankeit, Johannes (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Prescribed signal concentration on the boundary: Weak solvability in a chemotaxis-Stokes system with proliferation - Black, Tobias; Wu, Chunyan (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

A composite consisting of intermetallic Ni3Fe and nitrogen-doped carbon for electrocatalytic water oxidation: The effect of increased pyridinic nitrogen dopant - Liu, Dan; Zhai, Haichao; Hu, Jie; Pan, Ying; Xu, Gengsheng; Zhu, Chuhong; Yuan, Yupeng (Ceramics International)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Process Chemistry and Technology; Ceramics and Composites; Electronic; Optical and Magnetic Materials

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Carbon-Based Metal-Free Electrocatalysts: Past, Present, and Future - Zhai, Qingfeng; Pan, Ying; Dai, Liming (Accounts of Materials Research)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Chemical Engineering (miscellaneous)

Strain‐Engineered Nano‐Ferroelectrics for High‐Efficiency Piezocatalytic Overall Water Splitting - Su, Ran; Wang, Zhipeng; Zhu, Lina; Pan, Ying; Zhang, Dawei; Wen, Hui; Luo, Zheng‐Dong; Li, Linglong; Li, Fa‐tang; Wu, Ming; He, Liqiang; Sharma, Pankaj; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A universal electrochemical activation enabling lattice oxygen activation in nickel-based catalyst for efficient water oxidation - Hu, Jie; Jiang, Daochuan; Weng, Zhaoyue; Pan, Ying; Li, Zhongjun; Du, Haiwei; Yuan, Yupeng (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Cascaded dual-loop organic Rankine cycle with alkanes and low global warming potential refrigerants as working fluids - Abbas, Wameedh Khider Abbas; Vrabec, Jadran (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Der Einfluss der Besteuerung auf Managementanreize und die Nutzung von Bonusbanken - Dyck, Daniel (Junior Management Science)

Editorial: Schmalenbach IMPULSE: Will etwas in Bewegung setzen - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

CoViD-19 als Katalysator für die digitale Professionalisierung angehender Lehrpersonen? - Schwabl, Franziska; Vogelsang, Christoph (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Die CoViD-19-Pandemie ab Frühjahr 2020 und die pandemiebedingten Kontaktbeschränkungen hatten erhebliche Auswirkungen auf die studienbegleitenden Praxisphasen im Lehramtsstudium. Studierende, die ihr Praxissemester im Sommersemester 2020 absolvierten, waren in der Folge erheblich von Einschränkungen sowohl während der universitären Begleitveranstaltungen als auch in den Praxisschulen betroffen. Durch die überwiegende Umstellung von Präsenzformaten zu digitalem Lehren und Lernen auf Distanz ist die Annahme naheliegend, dass Studierende vermehrt die Möglichkeit hatten, Erfahrungen mit digitalen Lernformaten zu machen. Anhand einer Sekundäranalyse der Befragung einer Kohorte von Praxissemesterstudierenden der Universität Paderborn (N=362) kann allerdings gezeigt werden, dass der erwartete Möglichkeitsraum für eine digitale Professionalisierung keineswegs ausgeschöpft bzw. überhaupt genutzt wurde. Vielmehr zeigte sich, dass angehende Lehrpersonen digitale Medien vor allem dann in den eigenen Unterricht einbetten, wenn diese in der mentoriellen Begleitung thematisiert wurde oder während Hospitationen beobachtet werden konnte. Zudem deuten die Analysen an, dass ungünstige Professionalisierungsbedingungen an den Praxisschulen nur bedingt durch die universitären Anteile der Praxisphasen aufgefangen werden konnten. Für die Gestaltung der universitären Lehrpersonenausbildung ergibt sich daher u. a. die Notwendigkeit einer intensiveren Kooperation zwischen den verschiedenen Akteuren der drei Phasen der Lehrpersonenbildung.

Selbstreguliertes Lernen im berufsschulischen Übergangssystem - Daniel-Söltenfuß, Desiree; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Selbstreguliertes Lernen fördern - Lernen auf Distanz ermöglichen - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

Effectiveness of health-oriented leadership interventions for improving health and wellbeing of employees: a systematic review - Dannheim, Indra; Ludwig-Walz, Helena; Buyken, Anette; Grimm, Valerie; Kroke, Anja (Journal of Public Health)
Abstract Aim To identify and summarize the evidence for the effect of health-oriented leadership interventions on health and well-being outcomes at the employee level following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Moher et al. 2009). Subject and Methods A systematic search of relevant studies was conducted in multiple databases. Randomized controlled trials (RCTs), cluster-randomized controlled trials (cRCTs) and controlled before–after studies (CBAs) were included based on the following criteria: interventions that addressed supervisors, to raise awareness for the importance of health issues, teach mindfulness practices for conscious awareness, reduce stress and promote resources at the level of individual behavior, and evaluated the effect on at least one outcome of psychomental stress, absenteeism and well-being on the employee level. Results Of 6126 publications retrieved, ten studies were identified for analysis. Significant effects of leadership training were reported on exhaustion tendency, self-reported sickness absence, work-related sickness absence and job satisfaction in studies comparing health-oriented training programs to no intervention. Studies comparing health-oriented leadership training to other training did not report significant effects. Risk of bias was judged to be high in seven studies and unclear in three studies. Conclusion Evidence for the effectiveness of health-oriented leadership interventions on employees’ stress, absenteeism or well-being is judged to be low, clearly indicating the need for more and higher-quality research.
Keywords: Public Health; Environmental and Occupational Health

Zur Einführung in Kapitel 10 und 11 - Grimminger-Seidensticker, Elke; Brandl-Bredenbeck, Hans Peter; Gerlach, Erin; Krieger, Claus (Sportpädagogik. Eine Grundlegend)

Forschungsmethodische Zugänge - Grimminger-Seidensticker, Elke; Krieger, Claus (Sportpädagogik. Eine Grundlegung)

Des arbitrages éthiques face aux injonctions à la pratique physique dans les programmes de promotion de la santé : le cas des familles populaires en Europe - Grimminger-Seidensticker, Elke; Vieille Marchiset, G.; Knobé, S.; Aceti, M. (SociologieS.)

Der historische Muhammad in der islamischen Theologie. Zur Kriterienfrage in der Leben-Muhammad-Forschung - Ghaffar, Zishan

Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Zum Einfluss der Erstsprache auf den Gebrauch von Präpositionen. Eine kontrastive Analyse im Lernerkorpus MERLIN. - Weber, Tassja (Deutsch im Vergleich. Theorie, Praxis, Didaktik.)
Die Verknüpfung kontrastiver Linguistik und Didaktik ist in der linguistischen Forschung von besonderer Bedeutung und steht im Mittelpunkt dieses Bandes. Mit dem Band werden einige der Themen aus der internationalen Tagung Kontrastive Linguistik vertieft, die 2018 an der Universität Mailand stattfand. Die zwölf Beiträge fokussieren sowohl theoretisch als auch praxisorientiert wichtige Merkmale des Deutschen, das mit anderen Sprachen (wie Italienisch, Englisch und Spanisch) durch vielfältige Methoden (u.a. Korpuslinguistik und Textlinguistik) verglichen wird. Dabei präsentieren sie neue Perspektiven für den didaktischen Bereich und tragen somit zur Diskussion der Potenziale der kontrastiven Analysen in den Bereichen der Mehrsprachigkeit, der Syntax und der Phonetik/Phonologie bei.

Eigenvalue spectra of QCD and the fate of UA(1) breaking towards the chiral limit - Kaczmarek, Olaf; Mazur, Lukas; Sharma, Sayantan (Physical Review D)

Heavy quark momentum diffusion from the lattice using gradient flow - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, H.-T. (Physical Review D)

Sphaleron rate from Euclidean lattice correlators: An exploration - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, H.-T. (Physical Review D)

High-Performance Spectral Element Methods on Field-Programmable Gate Arrays : Implementation, Evaluation, and Future Projection - Karp, Martin; Podobas, Artur; Jansson, Niclas; Kenter, Tobias; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (2021 IEEE International Parallel and Distributed Processing Symposium (IPDPS))

The Form of Truth. Hegel’s Philosophical Logic. - Ficara, Elena

Quality Criteria for Conceptual Technology Integration Models in Education: Bridging Research and Practice. Educational Technology Research and Development - Tondeur, J; Petko, D; Christensen, R; Starkey, L; Drossel, Kerstin; Eichhorn, K; Schmidt-Crawford, D; Knezek, D (Educational Technology Research and Development)

Reconfigurable and Real-Time Nyquist OTDM Demultiplexing in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Electrical Engineering and Systems Science)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain demultiplexing of coherent multilevel Nyquist signals in silicon photonics. No external pulse source is needed and frequencytime coherence is used to sample the incoming Nyquist OTDM signal with orthogonal sinc-shaped Nyquist pulse sequences using Mach-Zehnder modulators. All the parameters such as bandwidth and channel selection are completely tunable in the electrical domain. The feasibility of this scheme is demonstrated through a demultiplexing experiment over the entire C-band (1530 nm - 1550 nm), employing 24 Gbaud Nyquist QAM signals due to experimental constraints on the transmitter side. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can demultiplex Nyquist pulses of 90 GHz optical bandwidth suggesting a possibility to reach symbol rates up to 90 GBd in an integrated Nyquist transceiver.

Unterstützung des Modellierungsprozesses durch Analogiebildung im Sachunterricht - Elsner, Julia; Tenberge, Claudia; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)

LIMES - A Framework for Link Discovery on the Semantic Web - Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Georgala, Kleanthi; Hassan, Mofeed; Dreßler, Kevin; Lyko, Klaus; Obraczka, Daniel; Soru, Tommaso (KI - Künstliche Intelligenz, German Journal of Artificial Intelligence - Organ des Fachbereichs "Künstliche Intelligenz" der Gesellschaft für Informatik e.V.)
The Linked Data paradigm builds upon the backbone of distributed knowledge bases connected by typed links. The mere volume of current knowledge bases as well as their sheer number pose two major challenges when aiming to support the computation of links across and within them. The first is that tools for link discovery have to be time-efficient when they compute links. Secondly, these tools have to produce links of high quality to serve the applications built upon Linked Data well. Solutions to the second problem build upon efficient computational approaches developed to solve the first and combine these with dedicated machine learning techniques. The current version of the LIMES framework is the product of seven years of research on these two challenges. A series of machine learning techniques and efficient computation approaches were developed and integrated into this framework to address the link discovery problem. The framework combines these diverse algorithms within a generic and extensible architecture. In this article, we give an overview of version 1.7.4 of the open-source release of the framework. In particular, we focus on an overview of the architecture of the framework, an intuition of its inner workings and a brief overview of the approaches it contains. Some descriptions of the applications within which the framework was used complete the paper. Our framework is open-source and available under a GNU license at https: //github.com/dice-group/LIMES together with a user manual and a developer manual.
Keywords: 2021 dice simba sherif limes ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limbo opal georgala kevin slipo sage

I-AID: Identifying Actionable Information from Disaster-related Tweets - Zahera, Hamada Mohamed Abdelsamee; Jalota, Rricha; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (IEEE Open Access)
Social media plays a significant role in disaster management by providing valuable data about affected people, donations and help requests. Recent studies highlight the need to filter information on social media into fine-grained content labels. However, identifying useful information from massive amounts of social media posts during a crisis is a challenging task. In this paper, we propose I-AID, a multimodel approach to automatically categorize tweets into multi-label information types and filter critical information from the enormous volume of social media data. I-AID incorporates three main components: i) a BERT- based encoder to capture the semantics of a tweet and represent as a low-dimensional vector, ii) a graph attention network (GAT) to apprehend correlations between tweets’ words/entities and the corresponding information types, and iii) a Relation Network as a learnable distance metric to compute the similarity between tweets and their corresponding information types in a supervised way. We conducted several experiments on two real publicly-available datasets. Our results indicate that I-AID outperforms state-of- the-art approaches in terms of weighted average F1 score by +6% and +4% on the TREC-IS dataset and COVID-19 Tweets, respectively.
Keywords: sys:relevantFor:infai sys:relevantFor:DAIKIRI ngonga zahera sherif daikiriproject dice simba

Multilingual Verbalization and Summarization for Explainable Link Discovery - Fathi Ahmed, Abdullah; Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Data & Knowledge Engineering)
The number and size of datasets abiding by the Linked Data paradigm increase every day. Discovering links between these datasets is thus central to achieving the vision behind the Data Web. Declarative Link Discovery (LD) frameworks rely on complex Link Specification (LS) to express the conditions under which two resources should be linked. Understanding such LS is not a trivial task for non-expert users. Particularly when such users are interested in generating LS to match their needs. Even if the user applies a machine learning algorithm for the automatic generation of the required LS, the challenge of explaining the resultant LS persists. Hence, providing explainable LS is the key challenge to enable users who are unfamiliar with underlying LS technologies to use them effectively and efficiently. In this paper, we extend our previous work (Ahmed et al., 2019) by proposing a generic multilingual approach that allows verbalization of LS in many languages, i.e., converts LS into understandable natural language text. In this work, we ported our LS verbalization framework into German and Spanish, in addition to English language. Our adequacy and fluency evaluations show that our approach can generate complete and easily understandable natural language descriptions even by lay users. Moreover, we devised an experimental neural approach for improving the quality of our generated texts. Our neural approach achieves promising results in terms of BLEU, METEOR and chrF++.
Keywords: 2021 sys:relevantFor:infai simba sherif ngonga ahmed limes dice raki moussallem libo opal knowgraphs

OntoConnect: Domain-Agnostic Ontology Alignment using Graph Embedding with Negative Sampling - Chakraborty, Jaydeep; Sherif, Mohamed; Zahera, Hamada Mohamed Abdelsamee; Bansal, Srividya (Proceedings of the IEEE International Conference on Machine Learning and Applications)
Keywords: dice sherif hamada

Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al. (Chemical Communications)
Two closely related FeII complexes with 2,6-bis(1-ethyl-1H-1,2,3-triazol-4yl)pyridine and 2,6-bis(1,2,3-triazol-5-ylidene)pyridine ligands are presented to gain new insights into the photophysics of bis(tridentate) iron(II) complexes. The [Fe(N^N^N)2]2+ pseudoisomer sensitizes singlet oxygen through a MC state with nanosecond lifetime after MLCT excitation, while the bis(tridentate) [Fe(C^N^C)2]2+ pseudoisomer possesses a similar 3MLCT lifetime as the tris(bidentate) [Fe(C^C)2(N^N)]2+ complexes with four mesoionic carbenes.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composite; Metallkomplexe; Optical and Magnetic Materials; Catalysis

Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Bericht von der 57. Jahrestagung des Leibniz-Instituts für Deutsche Sprache (als Online-Konferenz), 9. bis 11. März 2021 - Georgi, Christopher (Sprachreport)

Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Bericht von der 57. Jahrestagung des Leibniz-Instituts für Deutsche Sprache, 9. bis 11. März 2021 - Georgi, Christopher (Deutsche Sprache)

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

Bestimmung von flussigkeitsseitigen Stoffübergangskoeffizienten für strukturierte Packungen basierend auf hydrodynamischen Analogien - Kämper, Marek

The Creation of Illegal Migration in the German Confederation, 1815–1866 - Schubert, Michael (Migrations and Border Processes. Practices and Politics of Belonging and Exclusion in Europe from the Nineteenth to the Twenty-First Century)

Arbeit und Melancholie - Vöing, Nerea

„Nicht alles lässt sich digital lösen“ – Jetzt schlägt die Stunde moderner Konzepte, meint Hochschuldidaktikerin Nerea Vöing - Vöing, Nerea (DUZ Magazin)

Besondere Formate der hochschuldidaktischen Weiterbildung. Stand der Praxis inklusive Good Practice-Beispiele - Vöing, Nerea; Franke, Kathrin; Sekyra, Anita (Handbuch Hochschuldidaktik)

»Ich bin froh darüber, dass das so passiert ist« - Kordts-Freudinger, Robert; Bücker, Diana; Schulte, Rebecca; Vöing, Nerea (Hochschule auf Abstand)

„Evidenz“, was meinen Sie damit? – Eine Interviewstudie zum Verständnis von Hochschullehrenden vom Evidenzbegriff - Vöing, Nerea; Leschke, Jonas; Daumiller, Martin (ZFHE)

Grenzen der Musik? Deutschsprachige Narrative zu Musik und Geräusch in den 1950er-Jahren - Tumat, Antje (Musikwissenschaft der Vielfalt. Festschrift Rebecca Grotjahn zum 60. Geburtstag)
Keywords: Neue Musik

Neue Wege in die Biologie: Verstehen mit Modellen - Originale – Theorien – Modellierung - Meister, Johannes; Trier, Ulrike; Upmeier zu Belzen, Annette

Attachment representation and emotion recognition ability in children with ADHD and their parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Krischer, M.; Susewind, M. (International Journal of Environmental Research and Public Health)

Zur inklusiven Betreuung von Kindern mit (drohender) Behinderung in Kindertageseinrichtungen in Bayern und im Rheinland. Ein Studienvergleich - Kißgen, R.; Wirts, C.; Limburg, D.; Wertfein, M.; Franke, Sebastian; Wölfl, J.; Austermühle, J. (Frühförderung interdisziplinär)

Attachment Representation and Emotion Recognition Ability in Children with ADHD and Their Parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Susewind, M.; Krischer, M. (International Journal of Environmental Research and Public Health)

Die Anfänge der Internationalen Ferienkurse für Neue Musik aus Gender-Perspektive - Tumat, Antje (Gender und Neue Musik)

Infant-Father Attachment in Infants Born Preterm. A Brief Report - Kissgen, R.; Franke, Sebastian; Jorjadze, N.; Roth, B.; Kribs, A. (International Journal of Developmental Science)

Exploring the paths towards service growth in manufacturing companies - Harrmann, L.; Böhm, Eva; Eggert, A. (2021 AMA Winter Academic Conference)

Ein kaiserlicher Wüterich und zwei antagonistische Simons. Der „Nero furens“ als Beispiel aus dem Paderborner Jesuitendramenkorpus - Elit, Stefan (NlatJb 23)

The Impact of Virtual Reality, Augmented Reality, and Interactive Whiteboards on the Attention Management in Secondary School STEM Teaching - Erofeeva, Maria; Klowait, Nils Oliver (2021 7th International Conference of the Immersive Learning Research Network (iLRN))

The Impact of Virtual Reality, Augmented Reality, and Interactive Whiteboards on the Attention Management in Secondary School STEM Teaching - Erofeeva, Maria; Klowait, Nils (2021 7th International Conference of the Immersive Learning Research Network (iLRN))

Hochschule auf Abstand
Trotz massiver Förderungen für die Digitalisierung ist die Präsenzlehre noch immer der Standard an deutschen Hochschulen. Aufgrund des Physical Distancing im Zuge der Corona-Pandemie musste sie jedoch kurzfristig fast vollständig digitalisiert werden. Die Beiträge des Bandes bieten einen multiperspektivischen Zugang zu den damit verbundenen Herausforderungen und beleuchten, wie die verschiedenen Akteur*innen die Umstellung auf digitale Lehr- und Lernformate umgesetzt und erlebt haben. Durch die Zusammenführung der verschiedenen Sichtweisen können die Bedarfe und Wünsche der einzelnen Akteursgruppen zusammengebracht und bei der nachhaltigen Weiterentwicklung der Hochschullehre besser berücksichtigt werden.

Engaging a product-focused sales force in solution selling: interplay of individual- and organizational-level conditions - Salonen, Anna; Terho, Harri; Böhm, Eva; Virtanen, Ari; Rajala, Risto (Journal of the Academy of Marketing Science)
Abstract This study explains how manufacturers tackle the critical managerial challenge of transforming a product-focused sales force to undertake solution selling. Through an application of configurational theory, the authors explain how individual and organizational conditions combine to determine salespeople’s engagement in solution selling. Multilevel, multisource data from the sales organization of a global supplier of building solutions represent input from salespeople ( N = 184), solution champions ( N = 23), and sales managers ( N = 26). A fuzzy set qualitative comparative analysis reveals no single, optimal way to overcome transformation challenges. Rather, consistent with prior research, solution selling requires certain types of salespeople, because value-based selling is a necessary condition for successful engagement. Beyond this foundational condition, a heterogeneous sales force can be engaged, as long as the organization provides appropriate support that is tailored to individual salespersons’ needs. The findings affirm that this viable support can come from either sales managers or solution champions.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Online reviews generated through product testing: can more favorable reviews be enticed with free products? - Garnefeld, Ina; Krah, Tabea; Böhm, Eva; Gremler, Dwayne D. (Journal of the Academy of Marketing Science)
Abstract Online reviews have profound impacts on firm success in terms of sales volume and how much customers are willing to pay, yet firms remain highly dependent on customers’ voluntary contributions. A popular way to increase the number of online reviews is to use product testing programs, which offer participants free products in exchange for writing reviews. Firms that employ this practice generally hope to increase review quality and secure higher product rating scores. However, a qualitative study, experimental study, and multilevel analysis of a field study dataset of more than 200,000 online reviews by product testers combine to reveal that product testing programs do not necessarily generate higher quality reviews, nor better product ratings. Only in certain circumstances (e.g., higher priced products) does offering a product testing program generate these benefits for the firm. Therefore, companies should consider carefully if and when they want to offer product testing programs.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Outcome-based contracting from the customers' perspective: A means-end chain analytical exploration - Schaefers, Tobias; Ruffer, Stefan; Böhm, Eva (Industrial Marketing Management)
Keywords: Marketing

Schreiben als Schlüsselkompetenz? - Scharlau, Ingrid; Haacke, Stefanie; Karsten, Andrea; Lahm, Swantje (Handbuch Hochschuldidaktik)

Untersuchung von Polymer-Dry-Blends und Bewertung ihrer Verarbeitungseigenschaften für den Lasersinterprozess (Studienarbeit) - Gawlikowicz, Roland

Wettkampfbezogene Emotionen im Sport – ein Scoping-Review - Wetzel, Änne; Güldenpenning, Iris; Weigelt, Matthias (German Journal of Exercise and Sport Research)
Zusammenfassung Jegliche Art von Emotionen im Sport spielen vor allem in Wettkampfsituationen eine bedeutende Rolle, wenn es darum geht, zu einem bestimmten Zeitpunkt die optimale Leistung abzurufen. Emotionen können Auswirkungen auf der physiologischen, perzeptuell-kognitiven oder behavioralen Ebenen haben. Daher bildet den Schwerpunkt des vorliegenden Scoping-Reviews, die Untersuchung der Bedeutung wettkampfbezogener (state) Emotionen von Sporttreibenden. Die Literaturrecherche ergab 1126 Arbeiten, aus denen 15 Studien die Einschlusskriterien erfüllten. Diese wurden hinsichtlich ihrer Themenschwerpunkte betrachtet: 1) Emotionen, Kognitionen und Angst; 2) Emotionen, Leistungsbeurteilung und Stress; 3) Emotionen und Leistungsziele; 4) Unterschiede emotionaler Ausprägung im Geschlecht und Leistungsniveau; 5) Einfluss von Kausalzuschreibungen auf die Emotionen. Anschließend wurden die in den vorgestellten Studien verwendeten emotionserfassenden Messinstrumente betrachtet und vorgestellt. Zusammengefasst erscheint die Erfassung wettkampfbezogener (state) Emotionen rund um das sportliche Geschehen (vor, während, danach) ein wesentlicher Bestandteil der angewandten Sportpsychologie, davon abgeleiteter Emotionsregulationsstrategien und somit der optimalen Leistungserbringung zu sein, auch wenn der (deutschsprachigen) sportpsychologischen Praxis bisher nur begrenzte validierte Messinstrumente vorliegen.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Examining the Perceptual-Cognitive Mechanism of Deceptive Actions in Sports - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Experimental Psychology)
Abstract. In several kinds of sports, deceptive actions are used to hinder the anticipation performance of an opponent. During a head fake in basketball, a player turns the head to one side but passes the ball to the other side. A pass with a head fake generates a head-fake effect in the observer, which is characterized by slower and more error-prone responses to the pass direction as compared to passes without a head fake. Whereas the head-fake effect has been replicated several times, the question of its origin with dynamic stimuli has not been answered yet. The present study includes four experiments, which are conducted to examine the perceptual-cognitive mechanism underlying the effect by using the model of dimensional overlap ( Kornblum et al., 1990 ) and the additive factors logic ( Sternberg, 1969 ). Results point to multiple processes contributing to the head-fake effect for dynamic stimuli, which operate not only at a perceptual level but also at a level of response selection.
Keywords: General Psychology; Arts and Humanities (miscellaneous); Experimental and Cognitive Psychology; General Medicine

A question of (perfect) timing: A preceding head turn increases the head-fake effect in basketball - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Plos one)

Electric and conventional vehicle usage in private and car sharing fleets in Germany - Habla, Wolfgang; Huwe, Vera; Kesternich, Martin (Transportation Research Part D: Transport and Environment)
Keywords: General Environmental Science; Transportation; Civil and Structural Engineering

Zustandsüberwachung zur Prognose der Restlebensdauer von Gummi-Metall-Elementen unter Berücksichtigung systembasierter Unsicherheiten - Bender, Amelie
Eine zustandsbasierte Instandhaltungsstrategie reduziert das Risiko eines Ausfalls eines technischen Systems bei gleichzeitig hoher Ausnutzung und planbaren Instandhaltungsmaßnahmen. Das Ziel dieser Arbeit liegt in der Entwicklung einer Zustandsüberwachung für Gummi-Metall-Elemente. Die Herausforderungen dieser Zustandsüberwachung leiten sich aus dem viskoelastischen Verhalten sowie dem komplexen Degradationsverhalten der Elemente ab. Infolge der daraus resultierenden Unsicherheiten werden die Elemente heutzutage präventiv instandgehalten. In Lebensdauerversuchen der Gummi-Metall-Elemente werden drei Messgrößen detektiert. Dabei wird mit der Temperatur eine Messgröße identifiziert, die am geeignetsten zur Beschreibung des Zustands der Elemente ist. Generell wird die Genauigkeit einer Zustandsüberwachung durch verschiedene Unsicherheiten beeinflusst. Für die Prognose der nutzbaren Restlebensdauer der Gummi-Metall-Elemente wird das Partikelfilter, eine verbreitete modellbasierte Methode zur Zustandsüberwachung technischer Systeme, weiterentwickelt, um Unsicherheiten im Verhalten und der Degradation der Elemente zu berücksichtigen. Anhand der Ergebnisse wird belegt, dass aufbauend auf dieser Zustandsüberwachung die Ausnutzung der Gummi-Metall-Elemente in realen Anwendungen durch eine präventive Instandhaltung erhöht werden kann. Damit bildet diese Arbeit die Basis für zukünftige, prädiktive Instandhaltungskonzepte für diese Elemente. Weiterhin bestätigt die Arbeit, dass eine Berücksichtigung vorliegender Unsicherheiten zu einem frühen Zeitpunkt im Entwicklungsprozess des Zustandsüberwachungssystems empfehlenswert ist.
Keywords: Zustandsüberwachung; Prognose der Restlebensdauer; modellbasierte Prognose; Partikelfilter; Unsicherheiten; Gummi; Verlässlichkeit; Lebensdauerversuche; Predictive Maintenance

FLight: FPGA Acceleration of Lightweight DNN Model Inference in Industrial Analytics - Ghasemzadeh Mohammadi, Hassan; Jentzsch, Felix; Kuschel, Maurice; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (Machine Learning and Principles and Practice of Knowledge Discovery in Databases)

Neural Correlates of Augmented Feedback Processing are Associated to Short-Term Behavioral Changes and Automaticity in Motor Learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Predictive value of valence-dependent neural correlates of augmented feedback processing for behavioral adaptation and learning in extensive motor learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Neural Processing of Augmented Feedback is Valence-Dependent and Changes After Extensive Practice of a New Motor Task - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Changes in valence-dependent neural correlates of augmented feedback processing after extensive motor sequence learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Effects of an Intervention for Promoting Basic Motor Competencies in Middle Childhood - Strotmeyer, Anne; Kehne, Miriam; Herrmann, Christian (International Journal of Environmental Research and Public Health)
The development of motor competencies is necessary for participation in the culture of sport, exercise, and physical activity, which in turn supports the development of a healthy lifestyle. A lack of physical activity in childhood and deficits in motor performance emphasize the relevance of interventions for promoting basic motor competencies. However, there are research desiderata with regard to such interventions. This article describes an intervention program for promoting basic motor competencies in middle childhood (around 6 to 10 years of age). The intervention was investigated in a longitudinal study from June 2019 to January 2020 (n = 200; 58% girls, M = 8.84 years, SD = 0.63) at three primary schools. The intervention was conducted once a week in physical education (PE). The comparison group participated in regular PE. The intervention showed significant effects on basic motor competencies in object movement but not in self-movement. The results demonstrate that positive effects on basic motor competencies can be achieved with the help of a relatively simple intervention. Further longitudinal studies are desirable as a means of substantiating the results and developing evidence-based concepts to support children in their development in the best possible way.
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health

Repeating head fakes in basketball: Temporal aspects affect the congruency-sequence effect - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, W.; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Der Einfluss von Kontextinformationen auf den Blicktäuschungseffekt im Basketball - Güldenpenning, Iris; Barkey, Thies; Jackson, Robin C.; Weigelt, Matthias (Talententwicklung und Coaching im Sport. Abstractband der 53. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

A multirate variational approach to Nonlinear MPC - Lishkova, Y.; Cannon, M.; Ober-Blöbaum, Sina

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Hybrid Prediction Method for Remaining Useful Lifetime Estimation Considering Uncertainties - Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
Predictive Maintenance as a desirable maintenance strategy in industrial applications relies on suitable condition monitoring solutions to reduce costs and risks of the monitored technical systems. In general, those solutions utilize model-based or data-driven methods to diagnose the current state or predict future states of monitored technical systems. However, both methods have their advantages and drawbacks. Combining both methods can improve uncertainty consideration and accuracy. Different combination approaches of those hybrid methods exist to exploit synergy effects. The choice of an appropriate approach depends on different requirements and the goal behind the selection of a hybrid approach. In this work, the hybrid approach for estimating remaining useful lifetime takes potential uncertainties into account. Therefore, a data-driven estimation of new measurements is integrated within a model-based method. To consider uncertainties within the system, a differentiation between different system behavior is realized throughout diverse states of degradation. The developed hybrid prediction approach bases on a particle filtering method combined with a machine learning method, to estimate the remaining useful lifetime of technical systems. Particle filtering as a Monte Carlo simulation technique is suitable to map and propagate uncertainties. Moreover, it is a state-of-the-art model-based method for predicting remaining useful lifetime of technical systems. To integrate uncertainties a multi-model particle filtering approach is employed. In general, resampling as a part of the particle filtering approach has the potential to lead to an accurate prediction. However, in the case where no future measurements are available, it may increase the uncertainty of the prediction. By estimating new measurements, those uncertainties are reduced within the data-driven part of the approach. Hence, both parts of the hybrid approach strive to account for and reduce uncertainties. Rubber-metal-elements are employed as a use-case to evaluate the developed approach. Rubber-metal-elements, which are used to isolate vibrations in various systems, such as railways, trucks and wind turbines, show various uncertainties in their behavior and their degradation. Those uncertainties are caused by diverse inner and outer factors, such as manufacturing influences and operating conditions. By expert knowledge the influences are described, analyzed and if possible reduced. However, the remaining uncertainties are considered within the hybrid prediction method. Relative temperature is the selected measurand to describe the element’s degradation. In lifetime tests, it is measured as the difference between the element’s temperature and the ambient temperature. Thereby, the influence of the ambient temperature on the element’s temperature is taken into account. Those elements show three typical states of degradation that are identified within the temperature measurements. Depending on the particular state of degradation a new measurement is estimated within the hybrid approach to reduce potential uncertainties. Finally, the performance of the developed hybrid method is compared to a model-based method for estimating the remaining useful lifetime of the same elements. Suitable performance indices are implemented to underline the differences between the results.
Keywords: Hybrid prediction method; Multi-model particle filtering; Uncertainty quantification; RUL estimation

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Proceedings of the Seventeenth International Conference on Condition Monitoring and Asset Management (CM 2021))
Several methods, including order analysis, wavelet analysis and empirical mode decomposition have been proposed and successfully employed for the health state estimation of technical systems operating under varying conditions. However, where information such as the speed of rotating machinery, component specifications or other domain-specific information is unavailable, such methods are often infeasible. Thus, this paper investigates the application of classical time-domain features, features from the medical field and novel features from the highly comparative time-series analysis (HCTSA) package, for the health state estimation of rotating machinery operating under varying conditions. Furthermore, several feature selection methods are investigated to identify features as viable health indicators for the diagnostics and prognostics of technical systems. As a case study, the presented methods are evaluated on real-world and experimentally acquired vibration data of bearings operating under varying speed. The results show that the selected features can successfully be employed as health indicators for technical systems operating under varying conditions.
Keywords: Wind turbine diagnostics; bearing diagnostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection; fault detection; failure detection

Rule-based Diagnostics of a Production Line - Aimiyekagbon, Osarenren Kennedy; Muth, Lars; Wohlleben, Meike Claudia; Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
In the industry 4.0 era, there is a growing need to transform unstructured data acquired by a multitude of sources into information and subsequently into knowledge to improve the quality of manufactured products, to boost production, for predictive maintenance, etc. Data-driven approaches, such as machine learning techniques, are typically employed to model the underlying relationship from data. However, an increase in model accuracy with state-of-the-art methods, such as deep convolutional neural networks, results in less interpretability and transparency. Due to the ease of implementation, interpretation and transparency to both domain experts and non-experts, a rule-based method is proposed in this paper, for prognostics and health management (PHM) and specifically for diagnostics. The proposed method utilizes the most relevant sensor signals acquired via feature extraction and selection techniques and expert knowledge. As a case study, the presented method is evaluated on data from a real-world quality control set-up provided by the European prognostics and health management society (PHME) at the conference’s 2021 data challenge. With the proposed method, our team took the third place, capable of successfully diagnosing different fault modes, irrespective of varying conditions.
Keywords: PHME 2021; Feature Selection Classification; Feature Selection Clustering; Interpretable Model; Transparent Model; Industry 4.0; Real-World Diagnostics; Quality Control; Predictive Maintenance

Anomaly detection in hot forming processes using hybrid modeling - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2021 26th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Efficient semi-analytical simulation of elastic guided waves in cylinders subject to arbitrary non-symmetric loads - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (Ultrasonics)

HighPerMeshes – A Domain-Specific Language for Numerical Algorithms on Unstructured Grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz-Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Euro-Par 2020: Parallel Processing Workshops)
Solving partial differential equations on unstructured grids is a cornerstone of engineering and scientific computing. Nowadays, heterogeneous parallel platforms with CPUs, GPUs, and FPGAs enable energy-efficient and computationally demanding simulations. We developed the HighPerMeshes C++-embedded Domain-Specific Language (DSL) for bridging the abstraction gap between the mathematical and algorithmic formulation of mesh-based algorithms for PDE problems on the one hand and an increasing number of heterogeneous platforms with their different parallel programming and runtime models on the other hand. Thus, the HighPerMeshes DSL aims at higher productivity in the code development process for multiple target platforms. We introduce the concepts as well as the basic structure of the HighPerMeshes DSL, and demonstrate its usage with three examples, a Poisson and monodomain problem, respectively, solved by the continuous finite element method, and the discontinuous Galerkin method for Maxwell’s equation. The mapping of the abstract algorithmic description onto parallel hardware, including distributed memory compute clusters, is presented. Finally, the achievable performance and scalability are demonstrated for a typical example problem on a multi-core CPU cluster.
Keywords: tet_topic_hpc

Evaluating the Design Space for Offloading 3D FFT Calculations to an FPGA for High-Performance Computing - Ramaswami, Arjun; Kenter, Tobias; Kühne, Thomas; Plessl, Christian (Applied Reconfigurable Computing. Architectures, Tools, and Applications)

The HighPerMeshes framework for numerical algorithms on unstructured grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz‐Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Concurrency and Computation: Practice and Experience)
Keywords: tet_topic_hpc